(untitled) (Al-Qamar, 2021)
The factors, current socioeconomic situations, protection factors, and the level of awareness of the street children are all discussed in the research "The Factors Affecting Street Child Life among the Community of Nandi Pur Town Gujranwala." The Drop-in Center PAHCHAAN, which works for the welfare of street children, collaborated in the study, which was conducted in Nandi Pur Town and the surrounding area. By using convenience-based non-probability selection, the regions with the largest proportion of street children were chosen as a sample. A questionnaire was employed as a data collecting technique to get information from kids, and the information was gathered in a matter of 28 days. Therefore, it is advised that parents’ financial situation be improved through various income support programs, a campaign should be launched to raise awareness of children’s rights, in which the media and NGOs should play a significant role, and most importantly, the laws about child protection issues should be rigidly followed.